Simulation Research on Influence of Temperature Distribution on Deformation Permeability in Plate. (November 2020) - He, Chunyu; Guo, Jia; Wang, Shuncai; Jiao, Zhijie
Abstract: During the plate rolling process, the deformation permeability to the inside is one of the important factors that determine the quality of the final product. The permeability capacity that determines the deformation is not only related to the inlet thickness and reduction, but also closely related to the plate temperature distribution. Based on the finite element method, the steel plate thickness, reduction and initial temperature distribution are taken as the initial conditions of the simulation, and the thermo-mechanical coupling finite element simulation is carried out for different steel grades in the paper. After the rolling is completed, the equivalent strains of different nodes are extracted in the thickness direction to obtain the influence law of the temperature gradient distribution on the deformation permeability, which provides reference for the formulation and adjustment of the production process of the plate.